1993
DOI: 10.1016/0168-6445(93)90021-z
|View full text |Cite
|
Sign up to set email alerts
|

Response of Thiobacillus ferrooxidans to phosphate limitation

Abstract: Phosphate ion is an essential nutrient for all cells. Consequently, starvation for this component may constitute a stressing condition which affects the bioleaching capacity of the biomining microorganisms. Therefore, we have studied the manner in which the chemolithotroph Thiobacillus ferrooxidans responds to phosphate limitation. Under these circumstances the bacteria reduced its growth rate, capacity to oxidize ferrous iron and to fix CO,. Concomitant with these changes, the cells showed an increased synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…form filaments (Holmquist and Kjelleberg 1993). In agreement with our work, Seeger and Jerez (1993) showed that A. ferrooxidans strain R2 also forms filaments under phosphate starvation conditions. The mechanisms responsible for the elongation that occurs when bacterial cells are subjected to non-optimal temperatures and to phosphate starvation are not clear.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…form filaments (Holmquist and Kjelleberg 1993). In agreement with our work, Seeger and Jerez (1993) showed that A. ferrooxidans strain R2 also forms filaments under phosphate starvation conditions. The mechanisms responsible for the elongation that occurs when bacterial cells are subjected to non-optimal temperatures and to phosphate starvation are not clear.…”
Section: Resultssupporting
confidence: 91%
“…These proteins are involved in CO 2 fixation, and the decreased expression of these proteins at 40°C suggests that the ability of A. ferrooxidans to fix CO 2 may be affected by this stress condition, as previously observed by Seeger and Jerez (1993). Since carbon dioxide serves as the sole source of carbon for a diverse array of obligate chemolithoautotroph bacteria, alterations in carbon metabolism are expected to be related to CO 2 fixation.…”
Section: Downregulated Proteinsmentioning
confidence: 80%
See 2 more Smart Citations
“…Cells grown with phosphate limitation present a filamentous morphology due to a lack of cell division (31,32). Phosphate starvation studies show changes in the degree of synthesis of at least 25 proteins, some of which are exclusively synthesized under starvation conditions (30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%